Effects of Cerebral Blood Flow and White Matter Integrity on Cognition in CADASIL Patients - Yin, Xinzhen; Zhou, Ying; Yan, Shenqiang; Lou, Min (Frontiers in Psychiatry, 2019)
Background: It remains unclear whether the degree of white matter tract damage or cerebral hypoperfusion could better predict the global cognitive impairment in CADASIL. We sought to determine the independent effects of cerebral perfusion status and white matter integrity on cognition. Methods: We reviewed prospectively collected clinical and imaging data from genetically-confirmed CADASIL patients who underwent both arterial spin labeling (ASL) perfusion MRI and diffusion tensor imaging (DTI). We analyzed the cerebral blood flow (CBF), mean diffusion (MD) and fractional anisotropy (FA) by dividing the brain tissue into white matter hyperintensity (WMH) and normal appearing white matter (NAWM). Global cognitive function was evaluated by using Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). Results: Of the included 29 CADASIL patients, the age was 48.4 ± 7.9 years, and 17 (58.6%) were women. MD was significantly correlated with CBF in both WMH (r = -0.407, P = 0.035) and NAWM (r = -0.437, P = 0.023), after adjusting for age and WMH volume. MoCA score was obtained in thirteen patients, and was significantly correlated with CBF in both WMH (r = 0.742, P = 0.004) and NAWM (r = 0.659, P = 0.014). Both CBF in WMH (area under the curve, 0.767; 95% CI, 0.586-0.947, P = 0.015) and MD in WMH (area under the curve, 0.740; 95% CI, 0.557-0.924, P = 0.028) were good predictor for cognitive impairment (MMSE score < 27). However, multiple linear regression analysis revealed that global cognitive function was independently associated with CBF in WMH only (standardized β = 0.485, P = 0.015), after adjusting for age, gender, WMH volume, the presence of subcortical infarcts and DTI metrics. Conclusions: Our findings suggested that cerebral hypoperfusion was more strongly associated with global cognitive dysfunction than the severity of brain microstructural damage, supporting that CBF assessed by ASL could serve as a candidate imaging indicator for monitoring alterations of global cognitive function in CADASIL.